Morphological and histological study of the spleen in Hedgehog (Hemiechinus auritus) - Thekra Atta Ibrahim (Tikrit Journal of Pure Science)
The present study aimed to investigate the morphological description and histological structure of the spleen in Hedgehog (Hemiechinus auritus); the anatomical study revealed that spleen in Hedgehog was elongated, tongue-like shape, with blue red color. It is situated in the abdominal cavity in the left side of the stomach. The results of histological study revealed that the spleen was surrounded by a thick capsule composed of outer layer of mesothelial cells and an inner layer consist of dense fibrous connective tissue, contains collagen and elastic fibers with more smooth muscle fibers, trabeculae extend from dense fibrous connective tissue the capsule into the splenic parenchyma. The contained trabecular arteries, nerves and were composed mainly of connective tissue made of collagen, reticular and elastic fibers and more smooth muscle fibers. It is comprised of two functionally and morphologically distinct compartments, the red pulp and the white pulp. The white pulp was made of lymphatic nodules consists of the marginal zone forming the outermost edge of white pulp, the periarteriolar lymphatic sheeth (PALS), central arteries and germinal centers Containing the phagocytic and plasma cells and Retinae cells win lymphocytes of medium and small-sized. The present study revealed some of these terminate in the marginal sinus at the junction of the white pulp and the marginal zone, whereas others traverse the marginal zone to form the venous system of the red pulp, which named after the large, blood-filled sinuses. Histological examination also showed that the red pulp spleen in hedgehog composed from vascular tissue that contain pulp arteries, venous sinuses and splenic cords Within the spaces between the cords are megakaryocytes and blood cells. Results of the present study revealed that extramedullary hematopoiesis (EMH) a normal occurs of the splenic red pulp. Extramedullary hematopoiesis may include increased numbers of erythroid precursors, myeloid precursors, megakaryocytes